Interpretación ambiental de datos hidrogeoquímicos de la laguna continental de Castañeiras (Pontevedra, SW Galicia) - Martínez Graña, Antonio (Geographicalia, 2017)
In this paper is resented a hydrogeochemical characterization of Castineirasis lagoon (Pontevedra) considering the graphic representation system of Stiff and Piper.
Keywords: hydrogeology; graphic representation Stiffis; graphic representation Piperis; geochemistry anaysis.